Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen di Toko Jihan Shop Cilacap - Azmi Kurnia Ayu Puspita; Hakim Hakim; Syafi’ah Syafi’ah (Indo Publishing, 2026)
This study aims to determine and analyze the effect of service quality and price on customer satisfaction at Jihan Shop Store in Cilacap, both partially and simultaneously. This research employed a quantitative approach using a survey method. The population consisted of all customers of Jihan Shop Store Cilacap, with a total sample of 96 respondents selected through purposive sampling technique. Data were collected by distributing questionnaires, and the data analysis techniques included validity test, reliability test, classical assumption test, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) using SPSS software. The results of the study indicate that partially, service quality has a positive and significant effect on customer satisfaction. Price also has a positive and significant effect on customer satisfaction. Simultaneously, service quality and price have a significant effect on customer satisfaction, with an R² value of 61.7% at Jihan Shop Store Cilacap. This finding shows that the better the service quality and the more appropriate the pricing strategy implemented, the higher the level of customer satisfaction. This study concludes that service quality and price are important factors in improving customer satisfaction. Therefore, Jihan Shop Store Cilacap should maintain and enhance service quality while implementing competitive pricing strategies in order to create customer satisfaction and loyalty.